The PENGARUH KEMASAN DAN DURABILITY MAKANAN RINGAN BUATAN MALAYSIA TERHADAP ETNOSENTRISME KONSUMEN DI BATAM: PENGARUH KEMASAN DAN DURABILITY MAKANAN RINGAN BUATAN MALAYSIA TERHADAP ETNOSENTRISME KONSUMEN DI BATAM - Tiurniari Purba (LPPM Universitas Putera Batam, 2019)
This study aims to determine the effect of variable packaging and durability on consumer ethnocentrism in Batam, both partially and simultaneously. The background of this research is due to the rise of types of snack products made in Malaysia circulating in every type of retail in Batam, and very well-selling. This research will be analyzed quantitatively with a research tool using a questionnaire. The results of the questionnaire will be processed with the help of SPSS statistical software. As for what will be tested is the multiple regression test. Regression test results showed that the packaging had no effect on consumer ethnocentrism in Batam. While the durability variable shows a significant influence on consumer ethnocentrism. Simultaneously the F test shows that both packaging and durability affect ethnocentrism. While the determination coefficient test results indicate that the determination test output for the R Square value of 0.817 means that the magnitude of the contribution or contribution of the X1 and X2 variables of 82% to the Y variable and the rest of 18% is the influence of other variables not mentioned in this study. Keywords: Packeging, Durability, Etnosentrisme, Snack